FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR KOPI INDONESIA KE AMERIKA SERIKAT - Puspita Rona Almas Tahani; Sri Muljaningsih; Kiki Asmara (Politeknik Negeri Lhokseumawe, 2021)
Abstract:This study aims to examine how much influence the United States GDP, inflation, exchange rate, and production have on Indonesia's coffee exports to the United States. This study uses a quantitative approach with secondary data for 20 years from 2000 to 2019. The research method uses multiple linear regression analysis with IBM SPSS v.25.0. The results of this study indicate that simultaneously the United States GDP, inflation, exchange rate and production variables affect Indonesia's coffee exports to the United States. Partially the inflation variable does not have a significant effect on Indonesia's coffee exports to the United States. Meanwhile, the GDP variable of the United States of America has a positive and significant effect on Indonesia's coffee exports to the United States. The exchange rate and production variables have a negative and significant effect on Indonesian coffee exports to the United States.Keywords: GDP, Inflation, Exchange Rate, Production, Export